Embedded-probes diagnostics for the COMPASS upgrade tokamak: a concept. (1st November 2022) - Dimitrova, M.; Gerardin, J.; Podolnik, A.; Balner, V.; Mitov, M.; Adamek, J.; Duran, I.; Weinzettl, V.; Veselovsky, V.; Dejarnac, R.; Komm, M.; Hron, M.; et al.
Abstract: This article introduces a concept based on flush-mounted probes embedded in the limiters of the COMPASS-Upgrade tokamak. Main issues related to flush probe geometry are taken into account and discussed. Calculations of heat fluxes and the incident angle of the field lines on the different limiters using the PFCflux code are performed to support in probe arrangement optimization. Model current-voltage characteristics for a flush probe are simulated using the SPICE2 code and their dependence on the angle of incidence is studied. The results are used to predict the current to be collected by the flush probes for different magnetic fields and to examine the reliability of the proposed diagnostics. A discussion is included on the capability of the electronic system considered for the measurements.